Improving conditions definitions activity antifungal phenolic compounds wormwood (Artemisia absinthium) - Попова, Е. М.; Куйбіда, М. А.; Приліпко, В. О. (Problems of Environmental Biotechnology, 2015)
The methods of determining the fungicidal activity of drugs of different provenance. Chosen most sensitive method for determining the fungicidal activity. Methods of using the fungicide biological and chemical provenance. As fungicidal agents was elected copper sulfate and extract of wormwood (Artemisia absinthium).